Natural Functional SNPs in miR-155 Alter Its Expression Level, Blood Cell Counts, and Immune Responses - Li, Congcong; He, Huabin; Liu, An; Liu, Huazhen; Huang, Haibo; Zhao, Changzhi; Jing, Lu; Ni, Juan; Yin, Lilin; Hu, Suqin; Wu, Hui; Li, Xinyun; et al. (Frontiers in Immunology, 2016)
miR-155 has been confirmed to be a key factor in immune responses in humans and other mammals. Therefore, investigation of variations in miR-155 could be useful for understanding the differences in immunity between individuals. In this study, four SNPs in miR-155 were identified in mice (Mus musculus) and humans (Homo sapiens). In mice, the four SNPs were closely linked and formed two miR-155 haplotypes (A and B). Ten distinct types of blood parameters were associated with miR-155 expression under normal conditions. Additionally, 4 and 14 blood parameters were significantly different between these two genotypes under normal and lipopolysaccharide (LPS) stimulation conditions, respectively. Moreover, the expression levels of miR-155, the inflammatory response to LPS stimulation and the lethal ratio following Salmonella typhimurium infection were significantly increased in mice harboring the AA genotype. Further, two SNPs, one in the loop region and the other near the 3' terminal of pre-miR-155, were confirmed to be responsible for the differential expression of miR-155 in mice. Interestingly, two additional SNPs, one in the loop region and the other in the middle of miR-155*, modulated the function of miR-155 in humans. Predictions of secondary RNA structure using RNAfold showed that these SNPs affected the structure of miR-155 in both mice and humans. Our results provide novel evidence of the natural functional SNPs of miR-155 in both mice and humans, which may affect the expression levels of mature miR-155 by modulating its secondary structure. The SNPs of human miR-155 may be considered as causal mutations for some immune-related diseases in the clinic. The two genotypes of mice could be used as natural models for studying the mechanisms of immune diseases caused by abnormal expression of miR-155 in humans.